KEPUASAN KERJA SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL APARAT PEMERINTAH DAERAH - Mentari, Ni Gusti Ayunda Ratna; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the influence of budget participation to managerial performance of local government official with job satisfaction as a moderating variable. Respondents of this research is the Head of Department, Head of Section, and Head of the respective offices in the Badung regency SKPD. The sampling technique was used of purposive sampling. Data collected by using a questionnaire that was distributed as many 96 pieces and return a questionnaire which still numbered 96. Data analysis technique used by Moderated Regression Analysis (MRA). Based on the result of the analysis showed that the budget participation has positive effect on the performance of local government officials and job satisfaction has positive effect among budget participation to managerial performance of local government official.
Keywords: budget participation, performance of government official, job satisfaction